2013
DOI: 10.1186/2193-1801-2-439
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on genetic diversification and heterosis in autotetraploid rice

Abstract: Polyploidization has played an important role in plant evolution and is a pathway for plants to increase genetic diversification and to get higher heterosis comparing with that of diploid does. This study was undertaken to assess the genetic variation and relationships among 40 autotetraploid rice genotypes and their counterpart diploid cultivars with 99 SSR markers screened from published rice genome. The 99 SSR markers detected polymorphism among autotetraploid genotypes and revealed a total of 291 alleles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…We observed abnormal chromosome behavior (e.g. chromosome lagging at metaphases I and II) in a low percentage of PMCs during meiosis, suggesting that interactions between alleles at the Sa, Sb, and Sc loci (Sa Intersubspecific autotetraploid rice hybrids are robust plants with the potential to increase rice yield but suffer from low seed set (He et al, 2011b;Shahid et al, 2013b;Wu et al, 2013). We developed over 1,000 combinations of autotetraploid rice in our laboratory during 2002 to 2010 and found that partial pollen sterility is a major cause of low seed setting in intersubspecific autotetraploid rice hybrids.…”
Section: Coexpression and Cis-motif Analysis Of Meiosis-related Or Stmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed abnormal chromosome behavior (e.g. chromosome lagging at metaphases I and II) in a low percentage of PMCs during meiosis, suggesting that interactions between alleles at the Sa, Sb, and Sc loci (Sa Intersubspecific autotetraploid rice hybrids are robust plants with the potential to increase rice yield but suffer from low seed set (He et al, 2011b;Shahid et al, 2013b;Wu et al, 2013). We developed over 1,000 combinations of autotetraploid rice in our laboratory during 2002 to 2010 and found that partial pollen sterility is a major cause of low seed setting in intersubspecific autotetraploid rice hybrids.…”
Section: Coexpression and Cis-motif Analysis Of Meiosis-related Or Stmentioning
confidence: 99%
“…We developed over 1,000 combinations of autotetraploid rice in our laboratory during 2002 to 2010 and found that partial pollen sterility is a major cause of low seed setting in intersubspecific autotetraploid rice hybrids. Furthermore, we found that interactions between different alleles of hybrid pollen sterility loci (Sa, Sb, and Sc) caused low pollen fertility in autotetraploid rice hybrids (Zhao et al, 2006;He et al, 2011b;Wu et al, 2013). It took 4 years to generate the autotetraploid spp.…”
Section: Coexpression and Cis-motif Analysis Of Meiosis-related Or Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty seven SSR primers equally distributed on twelve chromosomes (McCouch et al, 2002) were analyzed. The SSR analysis was done as described by Tong et al (2011) and Wu et al (2013). The amplified fragments were electrophoresed on a 1.2% agarose gel at 80 V in 1X TBE buffer (Yang et al, 2012).…”
Section: Marker Analysismentioning
confidence: 99%
“…Many coworkers supported, molecular markers could be used for heterosis prediction (Jaikishan et al, 2010 andSoni et al, 2017), while others disagreed (Chen et al, 2010 andWu et al, 2013). However, technology proven a powerful tool for reliable heterosis prediction.…”
Section: Selection Of Marker Toolmentioning
confidence: 99%